EVALUATING ENGLISH TEXTBOOK CURRENTLY IN USE AT “ENGLISH BITES” (ENGLISH EXTRACURRICULAR PROGRAM EXISTED IN CIVIL AVIATION POLYTECHNIC OF SURABAYA) - Lusiana Dewi Kusumayati (Jurnal Penelitian)
Facing global competition in aviation Industry, the cadets of Politeknik Penerbangan Surabaya (Aviation Polytechnic of Surabaya) are suggested to take English extracurricular program held by POLTEKBANG language unit. It is in line with the institution’s policy for the cadets to pass TOEIC test as one of requirements before graduating from the college. The textbook used at the course is one of the key elements for the success of the program. Considering its importance, textbook should be carefully evaluated and selected before being used. Textbook evaluation helps the teaching staff to identify the strengths and weaknesses of a particular textbook that is already in use. This research seeks to evaluate the suitability of the book, “New Headway”, towards students’ needs. For this purpose, 25 students and 1 instructor were selected and data were gathered by using questionnaire. An additional component of the study consisted of a student’s “needs analysis”. After analyzing data, it was shown that although the textbook had some drawbacks, it had met the students’ need.